Fatty acid profile and oxidation stability of oil extracted from rainbow trout (Oncorhynchus mykiss) by-product by isoelectric solubilization/precipitation - Farideh Flahatgar Khomairan; Eshagh Zakipour Rahimabadi; Hanieh Rostamzad (تغذیه آبزیان, 2016)
This work was conducted to study the fatty acid profile of oil extracted from rainbow trout by-product by isoelectric solubilization/precipitation and its oxidation stability during 45 days refrigerated storage. After extraction and methylation of extracted oil, fatty acid profile was determined by gas liquid chromatography. Free fatty acid, peroxide value and thiobarbituric acid were measured in 15-day intervals to determine the hydrolytic and oxidation stability during 45 days. Twenty three  fatty acids were identified in acidic, basic and control samples. Extraction of oil by acidic and basic Isoelectric solubilization/precipitation affected neither the fatty acid profile  nor the content of ling chain fatty acids. n-3/ n-6 ratio were 0.148 and 0.172 in acidic and basic treatments, respectively. Atherogenic index and thrombogenic index in acidic and basic treatments were found to be 0.223 and 0.380, as well as 0.202 and 0.347, respectively. The extracted oils were stable to oxidation during 45-day storage in refrigerator.